Fabrication of polycaprolactone electrospun fibres with retinyl acetate for antioxidant delivery in a ROS-mimicking environment - Westwood, Lorna; Emmerson, Elaine; Callanan, Anthony (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Increased cancer rates denote that one in two people will be diagnosed with cancer in their lifetime. Over 60% of cancer patients receive radiotherapy, either as a stand-alone treatment or in combination with other treatments such as chemotherapy and surgery. Whilst radiotherapy is effective in destroying cancer cells, it also causes subsequent damage to healthy cells and surrounding tissue due to alterations in the tumor microenvironment and an increase in reactive oxygen species (ROS). This can cause extensive damage that impairs tissue function, and the likelihood of tissue regeneration and restoration of function is significantly reduced as new healthy cells cannot survive in the damaged environment. In the treatment of head and neck cancers, radiotherapy can cause salivary gland dysfunction. This significantly impairs the patient’s quality of life and there is currently no cure, only palliative treatment options. Tissue engineering approaches are used to mimic the microenvironment of the tissue and can mediate the damaged microenvironment via bioactive compounds, to support the delivery, survival, and proliferation of new, healthy cells into the damaged environment. Methods: In this study, retinyl acetate, a derivative of vitamin A, was successfully incorporated into electrospun polycaprolactone fibres. Results: SEM images and characterization analyses showed that all scaffolds produced had similar characteristics, including fiber morphology and scaffold wettability. The vitamin scaffolds were shown to exert an antioxidant effect through scavenging activity of both DPPH and hydroxyl radicals in vitro. Critically, the antioxidant scaffolds supported the growth of human submandibular gland cells and significantly upregulated the expression of GPx1, an antioxidant enzyme, when cultured under both normal conditions and under a simulated oxidative stress environment. Discussion: These results suggest that incorporation of retinyl acetate into electrospun fibres has may mediate the damaged microenvironment post cancer radiation therapy.